A SMALL AUXIN UP-REGULATED RNA Gene Isolated from Watermelon (ClSAUR1) Positively Modulates the Chilling Stress Response in Tobacco via Multiple Signaling Pathways - Duo Wang; Gangli Ma; Jia Shen; Xinyang Xu; Weisong Shou; Zhengying Xuan; Yanjun He (Horticulturae)
SMALL AUXIN UP-REGULATED RNA (SAURs) genes are acknowledged as auxin-responsive genes that play crucial roles in modulating adaptive growth under abiotic stress conditions. Low temperatures constitute a primary limiting factor that significantly impairs the development, growth, and fruit quality of watermelon plants during the winter and spring seasons. Despite their potential importance, SAURs have not yet been thoroughly investigated or characterized in watermelon. In this study, we identified a positive regulator of the chilling stress response among watermelon SAURs, designated as ClSAUR1. Subcellular localization analysis demonstrated that the protein is directed to both the nucleus and cytoplasm. Quantitative real-time PCR (qRT-PCR) analysis indicated that ClSAUR1 is ubiquitously expressed across various watermelon tissues, with pronounced expression in the roots and leaves. Moreover, qRT-PCR and promoter::β-glucuronidase (GUS) staining assays revealed that the expression of ClSAUR1 is significantly upregulated in response to exogenous abscisic acid (ABA) and chilling stress. The overexpression of ClSAUR1 in tobacco lines was contrasted and analyzed, revealing an increased tolerance to chilling stress. This was evidenced by a reduced degree of wilting and chlorosis compared to wild-type (WT) plants. Furthermore, the overexpressed lines showed reduced reactive oxygen species (ROS) accumulation and increased antioxidant enzyme activity. The qRT-PCR results further indicated that the expression levels of genes associated with abscisic acid (ABA), antioxidant enzymes, and CBF–COR cold-responsive pathways were upregulated in the transgenic tobacco lines. This study provides new insights into the role of ClSAURs in enhancing the cold resistance of watermelon.